The Powers of the Head of State in the Legislative and Executive Branch in Former Socialist Systems - Kobal, Aleš (Institute for Local Self-Government and Public Procurement Maribor, 2016)
This paper deals with the position and the powers of head of state in the legislative and the executive branch in former socialist systems. It examines the system in countries that emerged from socialist regimes, where the parliamentary system and the function of the President of the Republic as the individual head of state were introduced in the 1990s, namely in 10 (newest) Member States of the European Union. The paper elaborates on the position of the President of the Republic, the extent of the office's powers, and the resulting cooperation between the office of the President, the executive and legislative bodies, which is also one of the fundamental criteria of the standard classification of political regimes. The powers of the President in the field of legislation are the powers based on which the relationship between the President of the Republic and the legislative authority is established. The analyzed powers that the President exercises vis-à-vis the parliament are the powers of the President in relation to the adoption of an Act, the powers that the President of the Republic has in the domain of announcing parliamentary elections and convening a parliamentary sitting, as well as the powers in the domain of dissolving the parliament and announcing early elections. In the second part the paper focuses on the relationship between the President of the Republic and the government, and, consequently, the President's powers in the formation of the government and the appointing of state officials.